Promoting mental health and wellbeing in schools: the impact of yoga on young people's relaxation and stress levels - Hagen, Ingunn; Skjelstad, Solbjørg; Nayar, Usha Sidana (Frontiers in Psychology, 2023)
This study aimed to examine the experiences of students who were exposed to a yoga intervention in school. Findings revealed that practicing yoga made the young people more aware of their need to relax and had a positive impact on their mental health and well-being. We explore the emphasis on relaxation among the participants of our study and how relaxation is related to other aspects, such as their experience of stress and sleep habits. This article is based on qualitative data gathered from teenagers in Norway who participated in the Norwegian part of the European research project “Hippocampus: Promoting Mental Health and Well-being among Young People through Yoga.” The project introduced yoga to young people in schools with an emphasis on those in situations of disadvantage, including mental health issues and other challenges related to their background. Data were collected through nine individual, semi-structured interviews and 133 logs collected in the spring of 2019. The major themes identified through the interviews and log material included becoming more relaxed and becoming aware of the need to unwind. Thus, the focus on relaxation is based on the importance the participants attributed to this theme. Study results suggest that yoga enhanced the students’ awareness and skills as well as empowering them to make healthier lifestyle choices. We view the importance of relaxation from a salutogenic perspective with a focus on the factors that contribute to good health in contrast to a pathogenic perspective where curing diseases is the goal.